Effect of firm-specific and macroeconomic conditions on corporate cash holdings: evidence from FMCG companies in India / Reeti Gaur and Rajinder Kaur. - Gaur, Reeti; Kaur, Rajinder (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
This paper attempts to find out the effects of firm-specific and macroeconomic variables on corporate cash holdings. Panel data regression analysis was applied on the selected FMCG companies in India for the years2001-02 to 2016-17. The analysis showed that FMCG firms in India prefer keeping huge amounts of cash reserves and one of the preferred sources of cash holdings is cash flow. However, large scale and highly levered firms do not have large cash holdings. On the other hand, among the macroeconomic variables economic growth and bank lending rate play a significant role while amaking cash holding decisions. The paper has tried to fill the gap in previous literature that often ignore the role of macroeconomic elements in cash holding decisions.